Optical Fredkin gate assisted by quantum dot within optical cavity under vacuum noise and sideband leakage - Kang, Min-Sung; Heo, Jino; Choi, Seong-Gon; Moon, Sung; Han, Sang-Wook (NATURE PUBLISHING GROUP, 2020)
We propose a deterministic Fredkin gate which can accomplish controlled-swap operation between three-qubit states. The proposed Fredkin gate consists of a photonic system (single photon) and quantum dots (QDs) confined in single-sided cavities (two electron spin states). In our scheme, the control qubit is the polarization state of the single photon, and two electron spin states in QDs play the role of target qubits (swapped states by control qubit). The interaction between a photon and an electron of QD within the cavity (QD-cavity system) significantly affects the performance of Fredkin gate. Thus, through the analysis of the QD-cavity system under vacuum noise and sideband leakage, we demonstrate that reliable interaction and performance of the QD-cavity system with photonic state (photon) can be acquired in our scheme. Consequently, the Fredkin gate proposed in this paper can be experimentally implemented with high feasibility and efficiency.
Keywords: SINGLE-ELECTRON SPIN; MANIPULATION; LOCKING; QUBIT